Avctoritas Apostolica St. Martin in Trier AD 385/386 - Hattenhauer, Hans 1931-2015 (2015)
Avctoritas Apostolica - St. Martin in Trier AD 385/386. The transformation of the Christian church into the Roman Empire’s state-church in the 4th century gave rise to the question of how the relation between church and secular governments should to be ordered. It was partly answered AD 385/386 at Trier in the trial of the heretic bishop Priscilian before Emperor Maximus Magnus. Whereas Bishop Saint Martin maintained that the church should regulate its inner-ecclesiastical conflicts by its own sanctions only, the majority of bishops requested the emperor’s help in their fight against heresy. Martin’s protest was in vain. Maximus Magnus condemned and executed Priscilian. This case was the first Christian heresy trial by a secular-government in European history.
Keywords: Martin -- Tours, Bischof, Heiliger -- 316-397; Häresie